Heat and Mass Transfer between Coaxial Jets in the Pipe - N. E. Shishkin (Fundamental Research and Application of Physical Science Vol. 8, 2023)
The solution to many technical problems involves the organization of the swirling gas cooling flow, the selection of its parameters that ensure the stabilization of the central flow, and the thermal protection of the channel surface. Most of the works showing the effect of one or another parameter do not allow generalizing both their own experimental data and data of similar studies that would allow designing energy devices with the necessary performance characteristics. This chapter presents the results of experiments, conducted both by different researchers and the author. The study is devoted to the distribution of temperature and concentration of gases when mixing coaxial flows at the axis and at the channel wall. Changes in factors, such as the flow regime, the density ratio of both flows, the degree of twist of the peripheral jet, and the proportionality of flows were considered within a wide range of parameters. The temperature and kinematic characteristics of the flow in cross-sections along the channel length were studied, and generalizing dependences for wall thermal protection effectiveness at the channel axis and in the jet mixing layer were proposed.